Determination of the Effects of Z. officinale and Propolis Extracts on Intestinal Microbiology and Histological Characteristics in Broilers - Tekeli, A.; Kutlu, H.R.; Celik, L.; Doran, F. (International Journal of Poultry Science, 2010)
The purpose of this study is to explore the effects of Z.officinale and propolis extracts on intestine microbiology and histology in broilers as alternative growth promoters to antibiotics. One-day-old, Ross 308 male broiler chicks were used in the experiment. At the beginning of the experiment, seven treatment groups [negative control, positive control, Z. officinale, propolis and three different combinations of Z. officinale + propolis (0.5 + 0.5, 1 + 1 and 1.5 + 1.5)] were formed with similar mean weight, comprising 16 birds each. Each group was fed ad libitum for 42 days. Supplementation of Z. officinale and propolis extracts alone or in combination reduce Coliform bacteria (p